La incidencia de la institucionalización en las formas de socialización de los adultos mayores de la residencia Santa Catalina Labouré en el periodo julio – diciembre del 2013 - Rivadeneira Betancourt, Mariana Stefanía (2014)
The institution as such, can maintain a physical structure, however what it gives to the subject will vary according to the context of the time, and what the state dictates. Therefore, the institutions seek to accomplish a specific task or function, which is configured according to the discipline of the subject serving as an entity of control and protection of social order. In this way from the action field of an institution comes its social function and it would be established that all institutions act in the prevention and control from different fields of knowledge on the situations and populations. These knowledge generates architectonic logics that distribute specific functions in the spaces, regulates the behaviors and application of knowledge through production of techniques for the intervention and social control, simultaneously develop narratives and discourses that are incorporated into the subjects as preventive mechanisms.